Peran Guru dalam Mengembangkan Kreativitas Anak Usia Dini melalui Seni Hasta Karya - Muqorrobin, Syamsul; Fathoni, Tamrin (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2023)
Teachers have an important role in the success of student learning. In addition, teachers also have a role to foster children’s creativity. One of the efforts is through the creation of handicraft. By developing this work, the teacher has an important role as a facilitator and at the same time as a motivator. This research aims to describe the role of teachers in developing early childhood creativity at Al Hasan Kindergarten, Sukorejo, Ponorogo. This study uses a qualitative descriptive method with data collection techniques through documentation, observation, and interviews. Meanwhile, data analysis was carried out in the following steps: data reduction, presentation to drawing conclusions. Based on the research results, teachers have carried out their roles as facilitators and motivators for students. The role as a facilitator was manifested in the form of preparing the provision of equipment and media needed for learning activities. While the role as a motivator was manifested in the form of providing stimulus, motivation and reinforcement to students so that they try their best in each lesson. From the results of the study, it can be concluded that the teacher’s role as a facilitator and motivator at Al Hasan Sukorejo Kindergarten Ponorogo has been carried out well.